Exploring The Effect of Climate change on Unemployment in Somalia: Evidence from ARDL Approach. (1990 – 2023) (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the impact of climate change on unemployment in Somalia over the period 1990–2023 using the Autoregressive Distributed Lag (ARDL) bounds testing approach. The dependent variable is unemployment, while key climate variables average temperature and annual rainfall are complemented with macroeconomic controls including GDP growth, agriculture’s share in GDP, and inflation. The long-run results indicated that temperature exerts a statistically significant negative effect on unemployment. Rainfall changes show no significant long-run effect; however, lagged rainfall positively influences short-run job creation. GDP growth significantly reduces unemployment in both the long and short run, while inflation has a modest but significant negative long-run impact. Agriculture’s share, although negative, is not statistically significant in the long term. The error correction term confirms a stable long-run equilibrium, with approximately 61% of deviations from equilibrium corrected annually. These findings highlight the complex and time-dependent interplay between climate and labor market outcomes in Somalia. The study recommends integrating climate adaptation into employment policy, enhancing agricultural resilience, diversifying the economy, and strengthening data systems to support climate–employment decision-making